Real-time thermodynamic monitoring of split inverter ACs: amicrocontroller-driven investigation of performance - I Gede Artha Negara; Adi Winarta; Putu Wijaya Sunu; I Dewa Made Cipta Santosa; I Nyoman Suamir; I Gusti Agung Bagus Wirajati; I Dewa Gede Agus Tri Putra (Politeknik Negeri Lhokseumawe, 2024)
Recent technological advancements, particularly in air conditioning cooling systems, have led to rapid developments such as inverter technology. Inverter technology provides various advantages including energy savings compared to non-inverter air conditioners. Globally, the inverter modulates the compressor to continue operation despite reaching the set temperature. This study aimed to monitor the performance of split inverter air conditioners utilizing microcontroller technology. The microcontroller model employed was the ATmega2560, capable of logging each test parameter and displaying in real-time. Additionally, the ATmega2560 integrated sensors including the DS18B20 temperature sensor and PZEM 004-T multifunction electrical sensor. Monitoring occurred over one hour of operation on a 8525 Btu/h capacity split inverter AC. Experimental monitoring results showed the lowest Tsupply at T1 compared to other temperatures, reaching 8°C. At Treturn, both T1 and T2 exhibited identical decreasing trends to 25.5°C around 3000 s. The minimum power variation occurred at P5 relative to other variations. The average power consumption of the split inverter AC was approximately 750 W. The minimum energy consumption observed was at E5 during the study, while the maximum was at E1 with peak energy consumption of 0.96 kWh. Microcontroller-based experimental monitoring can provide real-time results and shows promise for monitoring split inverter AC performance.